Development and implementation of the lung volume reduction pulmonary rehabilitation tool to identify eligibility for lung volume reduction in people with chronic obstructive pulmonary disease during pulmonary rehabilitation - Buttery, Sara C; Williams, Parris J; Brighton, Lisa J; Batista, Craig; Dewar, Amy; Hogg, Lauren; Ingram, Karen; Korff, Gemma; Koulopoulou, Maria; Lammin, Helen; Maddocks, Matthew; McDonnell, Lynn; et al. (Chronic respiratory disease, 2023)
Background Completion of pulmonary rehabilitation is recognised in chronic obstructive pulmonary disease (COPD) guidelines as a key opportunity to consider systematically whether a respiratory review to assess potential suitability for a lung volume reduction (LVR) procedure might be appropriate. We describe the development of a simple decision-support tool (the LVR-PR tool) to aid clinicians working in pulmonary rehabilitation, to operationalise this process. Methods We took an iterative mixed methods approach, which was partnership-based and involved an initial consensus survey, focus groups and an observational study cohort at multiple pulmonary rehabilitation centres. Results Diagnosis (97%), exercise capacity (84%), breathlessness (78%) and co-morbidities (76%) were acknowledged to be essential items for assessing basic LVR eligibility. Collating prior investigations and assessing patient understanding were considered useful but not essential. Clinician concerns included; streamlining the tool; access to clinical information and investigations; and care needed around introducing LVR therapies to patients in a PR setting. Access to clearer information about LVR procedures, the clinician’s role in considering eligibility and how educational resources should be delivered were identified as important themes from patient group discussions. The LVR-PR tool was considered to be feasible and valid for implementation in a variety of PR services across the UK subject to the provision of appropriate health professional training. Clinicians working in specialist LVR centres across the UK who were not otherwise involved in the development process confirmed the tool’s validity using the content validity index (CVI). Interpretation The LVR-PR tool appears to be an acceptable tool that can be feasibly implemented in PR services subject to good quality educational resources for both patients and healthcare professionals.